Interoceptive differences in elite sprint and long-distance runners: A multidimensional investigation - Seabury, T.; Benton, D.; Young, H. A. (PLOS ONE, 2023)
Interoception, the process of detecting and interpreting bodily sensations, may facilitate self-regulation and thereby play a crucial role in achieving elite performance in competitive sports. However, there is a lack of research conducted in world-class athletes. In the present research, two studies examined self-reported (interoceptive sensibility) and behavioural (interoceptive accuracy) interoception in elite (top 100 ranking) sprint and long-distance runners, and non-athletes. Study 1 used the Multidimensional Assessment of Interoceptive Awareness Questionnaire. Sprinters reported having better regulation of attention to internal sensations, greater emotional awareness, better self-regulation, and reported a greater propensity to listen to their body for insight, than distance runners. Compared to non-athletes, sprinters and distance runners had more bodily trust, attention regulation, and self-regualtion. Additionally, elite athletes reported lower emotional awareness, self-regulation, and body listening. Study 2 examined cardioception using two tasks: The Heartbeat Counting Task, and The Heartbeat Detection Task. Elite and non-elite runners performed the tasks under two conditions; in silence, and whilst listening to pre-recorded crowd noise that simulated the live sounds of spectators during a sporting event. Sprinters and distance runners were able to maintain heartbeat detection accuracy when distracted, whereas non-athletes could not. Across both tasks, compared to non-athletes, sprinters and distance runners were more confident than non-athletes in their interoceptive percept. Additionally, elite athletes compared to non-elite athletes were less accurate when counting their heartbeat and were characterised by a higher interoceptive prediction error. Athletic populations have altered interoceptive abilities.